Associations Between Acute Conflict and Maternal Care Usage in Egypt: An Uncontrolled Before-and-After Study Using Demographic and Health Survey Data - Saji S. Gopalan; Richard J. Silverwood; Omar Salman; Natasha Howard (International Journal of Health Policy and Management, 2019)
Background United Nations’ (UN) data indicate that conflict-affected low- and middle-income countries (LMICs) contribute considerably to global maternal deaths. Maternal care usage patterns during conflict have not been rigorously quantitatively examined for policy insights. This study analysed associations between acute conflict and maternal services usage and quality in Egypt using reliable secondary data (as conflict-affected settings generally lack reliable primary data).